Cerebrospinal fluid protein carbonylation identifies oxidative damage in autoimmune demyelination. Issue 2 (20th December 2016) - Irani, David N.
Abstract: Oxidative damage occurs in multiple sclerosis, but is difficult to identify antemortem and remains an unknown contributor to disease progression. Carbonylation is a quantitative measure of protein oxidation. Cerebrospinal fluid samples from multiple sclerosis patients showed elevated carbonylated protein levels compared to controls. In experimental autoimmune encephalomyelitis, carbonylated protein levels in cerebrospinal fluid correlated tightly with those found in inflamed spinal cord tissues. Furthermore, concentrations in cerebrospinal fluid and spinal cord responded in parallel to an antioxidant intervention that also attenuated disease symptoms. These data suggest that carbonylated cerebrospinal fluid proteins could be a quantitative, sensitive, and disease‐relevant biomarker in multiple sclerosis.